Learning Environment as Correlate of the Mathematical-Logical Intelligence - Istirohah, Inova (Papanda Publisher, 2022)
This study aims to determine the relationship between the atmosphere of the learning environment and the mathematical-logical intelligence of the fifthgrade students in SD N 1 Tersobo. The approach used is a quantitative approach and the type of research is correlational. The population of this research is the fifthgrade students of SD N 1 Tersobo. The sampling technique used is saturated sampling. Data was collected by means of interviews, distributing questionnaires and tests. Data analysis by means of: analysis prerequisite test includes normality test and linearity test and followed by hypothesis testing with correlation test. The results is a positive and significant relationship between the atmosphere of the learning environment and mathematical-logical intelligence students with an r value of 0.392. This shows that there is a positive and significant relationship between the atmosphere of the learning environment and Mathematical-Logical intelligence.